2009
DOI: 10.1098/rspa.2009.0117
|View full text |Cite
|
Sign up to set email alerts
|

Dating fired-clay ceramics using long-term power law rehydroxylation kinetics

Abstract: Fired-clay materials such as brick, tile and ceramic artefacts are found widely in archaeological deposits. The slow progressive chemical recombination of ceramics with environmental moisture (rehydroxylation) provides the basis for archaeological dating. Rehydroxylation rates are described by a (time) 1/4 power law. A ceramic sample may be dated by first heating it to determine its lifetime water mass gain, and then exposing it to water vapour to measure its mass gain rate and hence its individual rehydroxyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
166
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(173 citation statements)
references
References 27 publications
6
166
1
Order By: Relevance
“…Wilson et al (2003) showed evidence that moisture expansion in fired-clay bricks and the associated mass gain increases as the fourth root of the time since firing (the RHX power-law model). Further reports (Savage et al 2008a,b;Wilson et al 2009) have confirmed this power-law model, and in the case of moisture expansion over periods of more than 50 years (Hall et al 2011). Thus, the RHX rate equation is given as y = a(T )t 1/4 , (2.1)…”
Section: Rehydroxylation and The Rhx Kinetic Modelmentioning
confidence: 83%
See 1 more Smart Citation
“…Wilson et al (2003) showed evidence that moisture expansion in fired-clay bricks and the associated mass gain increases as the fourth root of the time since firing (the RHX power-law model). Further reports (Savage et al 2008a,b;Wilson et al 2009) have confirmed this power-law model, and in the case of moisture expansion over periods of more than 50 years (Hall et al 2011). Thus, the RHX rate equation is given as y = a(T )t 1/4 , (2.1)…”
Section: Rehydroxylation and The Rhx Kinetic Modelmentioning
confidence: 83%
“…In an earlier paper (Wilson et al 2009), we set out the principles of rehydroxylation (RHX) measurements on fired-clay bricks and tiles, and we noted that this method of dating should be applicable to archaeological pottery. Here we present the first results of applying RHX dating to three types of archaeological pottery, varying in age, type and depositional environment.…”
Section: Introductionmentioning
confidence: 99%
“…In this way not only was a master function defining strict least upper bounds on T c established (11) (14). Percolative rehydroxylation is characteristic of ceramics and can be used to date them (15).…”
Section: Percolation | Theorymentioning
confidence: 99%
“…Drying is an unavoidable preconditioning procedure for gas permeability [11,16], gas adsorption [17], gas diffusion [18] and water absorption [19,20]. However, despite the existence of numerous drying methods for PC samples [21][22][23], no drying methods have specifically been developed for AASC to date.…”
Section: Introductionmentioning
confidence: 99%